Androgen receptor gene mutations are associated with male infertility in Northeast China: Clinical features and identification of two novel mutations. (8th November 2018) - Li, Leilei; Yang, Xiao; Wang, Ruixue; Liu, Xiaojun; Yu, Yang; Feng, Tao; Liu, Ruizhi; Zhang, Guirong
Abstract: The purpose of this study was to investigate the prevalence of androgen receptor gene mutations in idiopathic male infertility in north‐east China and to analyse the relationship between genotype and phenotype. Cohorts of 400 male patients with idiopathic infertility and 200 fertile controls were recruited. Clinical investigations were carried out by experienced andrologists. Targeted exome sequencing was used to detect androgen receptor gene mutations, and reproductive hormone levels were measured. We found four mutations in 8/400 patients (2%) and no mutations in controls. In addition, two recurrent mutations (p.S176R and p.A403V) were found in four patients and two patients respectively. Of four mutations, two (p.S233F and p.H715N) represented novel mutations. Almost all of the men with androgen receptor gene mutations showed smaller testicular volumes. However, the reproductive hormone levels were normal or lightly higher in seven men with mutation, apart from one man (P24) who had high follicle‐stimulating hormone and luteinising hormone levels but a low testosterone level. In north‐east China, there was a higher androgen receptor gene mutation rate among these infertile men, and the mutation of p.S176R deserved more attention particularly. Hormone levels and clinical phenotypes did not help in screening patients at risk of mutations.